Genetic differentiation among Atlantic island populations of the brown spiny lobster Panulirus echinatus (Decapoda: Palinuridae). Issue 5 (7th February 2020) - Gaeta, Juliana; Acevedo, Iván; López‐Márquez, Violeta; Freitas, Rui; Cruz, Raúl; Maggioni, Rodrigo; Herrera, Rogelio; Machordom, Annie
Abstract: Declines in Panulirus echinatus Smith, 1869 populations along their wide distribution in the Atlantic Ocean have spurred efforts to improve their fisheries management and conservation. In this study, the genetic structure of these populations is reported for the first time. In a survey of 18 species‐specific polymorphic microsatellite markers, 152 individuals were genotyped from five Atlantic oceanic islands, covering most of the insular distribution range of the species. The analyses revealed that P. echinatus is genetically partitioned into two stocks in the Atlantic Ocean. A highly significant genetic structure was observed between north‐east and south‐west Atlantic populations based on fixation index, discriminant analysis of principal components, and structure and barrier analysis. We suggest that the Equatorial Circulation System represents a biophysical barrier that effectively limits migration among Atlantic subtropical gyre systems, as has been described for other species. Other physical and ecological barriers, such as the Mid‐Atlantic Ridge itself, the distance between the eastern and western sides of the Atlantic (Mid‐Atlantic Barrier) and water mass differences, as well as other biological aspects, may also influence larval dispersal and modulate the insular distribution of this species. The results show the existence of two distinct genetic stocks of P. echinatus and have implications for fisheries management in the Atlantic Ocean, including their independent management according to their individual status. The Cabo Verde and the Canarian populations (north‐east Atlantic) showed the lowest level of genetic variability in comparison with the south‐western populations. A combination of factors that have occurred or are occurring in the Canary Islands, such as overfishing and volcanic eruptions, is likely to explain the reduced abundance of this lobster species in the area.